(untitled) (Web of Teachers: Inderscience Research, 2026)
This study is aimed at determining the effectiveness of innovative pedagogical technologies in teaching the topic of quantum dot biosensors to medical students. During the research process, modern educational approaches were applied, including multimedia tools, interactive methods, and virtual laboratory technologies. These approaches contributed to deepening students’ theoretical knowledge, improving their understanding of complex scientific concepts, and developing practical skills. The results of the study showed that the use of innovative pedagogical technologies is an important factor in enhancing the effectiveness of medical education, increasing student engagement, and fostering their professional competencies. In addition, it was found that this approach significantly optimizes the process of mastering complex nanobiotechnological topics.